2020
DOI: 10.1093/cz/zoaa026
|View full text |Cite
|
Sign up to set email alerts
|

Infant attraction: why social bridging matters for female leadership in Tibetan macaques

Abstract: Leadership is a key issue in the study of collective behavior in social animals. Affiliation-leadership models predict that dyadic partner preferences based on grooming relationships or alliance formation positively affect an individual’s decision to follow or support a conspecific. In the case of many primate species, females without young infants are attracted to mother-infant dyads. However, the effects of mother-infant-female associations on affiliation-leadership models remain less clear. In free-ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…Previous studies have shown that social centrality plays a key role in the success of collective movements in Tibetan macaques, where individuals demonstrating higher social centrality are more likely to succeed in initiating the group movement [ 28 ]. The eigenvector centrality coefficient measures how closely associated an individual is to others in group movements [ 42 ]. Thus, it is suggested that individuals with high social centrality possessed a stronger social affinity and could interact with more followers through vocal communication.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that social centrality plays a key role in the success of collective movements in Tibetan macaques, where individuals demonstrating higher social centrality are more likely to succeed in initiating the group movement [ 28 ]. The eigenvector centrality coefficient measures how closely associated an individual is to others in group movements [ 42 ]. Thus, it is suggested that individuals with high social centrality possessed a stronger social affinity and could interact with more followers through vocal communication.…”
Section: Discussionmentioning
confidence: 99%
“…This site consists of deciduous broadleaf and broadleaf evergreen mixed forests at altitudes from 600–1200 m [ 31 , 41 ]. Several wild groups of Tibetan macaques live in this area [ 31 , 42 ]. We focused our data collection on the Yulingkeng A1 (YA1) group (group size: 27–40 individuals), which has been provisioned and observed since 1986 [ 31 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…We also calculated the eigenvector centrality coefficient via HWI matrices using SOCPROG 2.4. Eigenvector centrality coefficient measures how closely associated an individual is to others in group movements ( Wang et al 2015 , 2020 ). A higher score of the eigenvector centrality coefficient indicates that the individual possesses more movement partners ( Newman 2004 ).…”
Section: Methodsmentioning
confidence: 99%
“…Potential conflicts of interest in Tibetan macaques represent consensus costs. Individuals must regularly negotiate conflicting interests among group mates that vary in their optimality criteria ( Wang et al 2020 ). This prerequisite requires the majority of group members to choose between collective decisions and individual choice, representing a compromising process.…”
mentioning
confidence: 99%